Identidade de gênero, futebol e videogames - Azevedo, Rogério Tenório de (2014)
This work aims to discuss the women´s exclusion from the design of soccer videogames. We investigated two of the best-selling videogames in Brazil titled Pro Evolution Soccer and FIFA Soccer. The research developed in three stages. First we observed the gameplay of five students, four males and a female, from a public school to analyze both the game design and the relationship between the game and the players. Then we conducted a bibliographical study in order to identify why these videogames exclude women´s soccer. It was possible to identify various contexts that contribute directly or indirectly to such exclusion. Finally, we proposed an activity on the exclusion of women´s soccer to the students in the same school to investigate how they understood this exclusion in the physical and digital soccer. The work had the research of Consalvo (2013) and Bryce, Rutter and Sullivan (2006), Crawford (2009), and Crawford and Gosling (2005) on gender identity and sports videogames as the main reference. We understood that the exclusion of women´s soccer cannot be attributed to a single reason. Both videogames seek to replicate the reality of soccer and the transmission broadcast of it on television but from contexts where women´s soccer has been marginalized. Moreover, the female audience has not been considered by the producers as an ideal market, despite its great consuming potential. As a result of the exclusion of women´s soccer from the design of videogames, soccer videogames are perceived as a male amusement, this could lead to a disengagement from practice for the women. Moreover, as a result of this exclusion, students had little knowledge about the women´s game. Therefore, it is necessary to reframe soccer videogames beyond mere amusement, as they may contribute to consolidate traditional values and concepts that position women at a disadvantaged place in sports and society.